Dampak Media Sosial Dalam Perubahan Ekonomi Di Tengah Masyarakat (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The impact of social media on economic changes in society can be seen from various aspects. Social media has had a significant impact especially in consumer behavior, marketing and business interactions. Apart from that, social media also influences people's social and economic behavior patterns, such as adapting to new habits, communication patterns, and creating a digital entrepreneurial ecosystem. Social media also has positive impacts, such as making interaction easier, expanding reach, and obtaining information at lower costs. However, there are also negative impacts, such as decreased face-to-face interaction, potential for addiction, conflict, and privacy issues. The use of social media has also initiated changes in social and economic behavior, for example in the case of farmers switching to the agrotourism sector due to social media activities, as well as influencing the presence of agrotourism and collaboration with outside parties. Thus, it can be concluded that social media has a significant role in shaping social and economic change in society, both in positive and negative terms.